Conditional political budget cycles in Argentine provinces - Daniel Lema (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
This paper presents evidence of electoraly-motivated changes in the budget balance, public expenditures, composition of public expenditures and provincial revenues in Argentine provinces. The empirical study is made using panel data analysis for 22 provinces during the period 1985-2001. Unconditional results show that conditioning on the alignment of provincial and federal executives (same political party in power) there is evidence of systematic changes in fiscal policies around elections. The observed changes support the predictions of rational opportunistic models of PBC. In election years, total provincial expenditures increase in aligned provinces, without affecting the fiscal balance, because to the increased discretional transfers from the federal government supporting the provincial incumbent federal revenues. By contrast, deficit increases for unaligned provinces. In addition, expenditure shifts toward current spending and away from capital spending for unaligned provinces in electoral years.
Keywords: D72; E62; 330; Politischer Konjunkturzyklus; Neue politische Ökonomie; Länderfinanzen; Argentinien